Theory of Cryptography 13th International Conference, TCC 2016-A, Tel Aviv, Israel, January 10-13, 2016, Proceedings, Part I - Kushilevitz, Eyal; Malkin, Tal (Security and Cryptology ;, 2016)
The two-volume set LNCS 9562 and LNCS 9563 constitutes the refereed proceedings of the 13th International Conference on Theory of Cryptography, TCC 2016, held in Tel Aviv, Israel, in January 2016. The 45 revised full papers presented were carefully reviewed and selected from 112 submissions. The papers are organized in topical sections on obfuscation, differential privacy, LWR and LPN, public key encryption, signatures, and VRF, complexity of cryptographic primitives, multiparty computation, zero knowledge and PCP, oblivious RAM, ABE and IBE, and codes and interactive proofs. The volume also includes an invited talk on cryptographic assumptions. .